Fabry disease: A single-center experience - Ergün Parmaksız; Meral Meşe (Ukrainian Journal of Nephrology and Dialysis, 2021)
Fabry disease (FD) is an inborn X-linked lysosomal storage disorder resulting from α–galactosidase A (α-Gal) activity deficiency in lysosomes. This results in the accumulation of particularly globotriaosylceramide (Gb3) within lysosomes in a wide variety of cells. This study aimed to analyze the clinical presentation, findings and family screenings of index cases, management and outcomes of  FD patients in our center.Methods. Data including demographic characteristics, personal history of comorbidities, laboratory findings at the time of diagnosis were recorded. α – Gal activity was measured in all males and females as initial analysis. The cut-off trigger was determined as 1.2 mmol/L per hour. Mutation analysis was performed in males and females with decreased α – Gal activity as a diagnostic assay. In addition, mutation analysis was performed change in females with normal α – Gal providing they have clinical signs or family history for FD.Results. The individuals from nine FD families were presented.Conclusion. Screening for genetic diseases such as FD has crucial conclusions. The detection of FD in an index case leads to appropriate therapy for that patient. Family screening can be started and additional undiagnosed individuals can be detected.